Immunogenicity and protective efficacy against Salmonella C2-C3 infection in mice immunized with a glycoconjugate of S. Newport Core-O polysaccharide linked to the homologous serovar FliC protein - Ofir Schuster; Khandra T. Sears; Girish Ramachandran; Fabien J. Fuche; Brittany Curtis; Sharon M. Tennant; Raphael Simon (Taylor & Francis Group, 2019)
Nontyphoidal Salmonella (NTS) are important human enteric pathogens globally. Among the different serovars associated with human NTS disease, S. Newport (a serogroup C2-C3 Salmonella) accounts for a measurable proportion of cases. However, to date there are no licensed human NTS vaccines. NTS lipopolysaccharide-associated O polysaccharides are virulence factors and protective antigens in animal models. As isolated molecules, bacterial polysaccharides are generally poorly immunogenic, a limitation overcome by conjugation to a protein carrier. We report herein the development of a candidate serogroup C2-C3 glycoconjugate vaccine based on S. Newport Core-O polysaccharide (COPS) and phase 1 flagellin (FliC). S. Newport COPS and FliC were purified from genetically engineered reagent strains, and conjugated at the polysaccharide reducing end to FliC protein lysines with thioether chemistry. S. Newport COPS:FliC immunization in mice improved anti-polysaccharide immune responses, generated high anti-FliC IgG titers, and mediated robust protection against challenge with both the homologous serovar as well another serogroup C2-C3 serovar (S. Muenchen). Analyses of S. Newport COPS:FliC induced sera found that the anti-COPS IgG antibodies were specific for serogroup C2-C3 lipopolysaccharide, and could promote bactericidal killing by complement and uptake into phagocytes. These preclinical studies establish the protective capacity of serogroup C2-C3 OPS glycoconjugates, and provide a path forward for the development of a multivalent Salmonella vaccine for humans that includes serogroup C2-C3.